Vehicle routing with shortest path system based Floyd Warshall Technique - Talib, Mohamad Shukor; Hasan, Haswadi; Abi Khallad, Nor Shahida (2006)
Vehicle routing plays an important role in courier industry. Problems normally occur during delivery process specifically in determine the receiver. From the practical point of view, solving this problem and have a good routing procedure can save the industry millions of dollars per year through cost-effective movement and delivery of goods. In addition, effective routing can increase productivity, improve operations and make the job of dispatching easier. This project was to develop a system that capable to determine the vehicle route by implementing the traditional method, Floyd Warshall. This system focus on area in a city in Penang and consider 46 locations as the case study. The system was developed in windows XP environment and the interface development developed by using Macromedia Dreamweaver 2004. Its database used Microsoft SQL server. This system was capable to give travel distance, and determine the sequence of location for goods delivery with the shortest path. The system has been tested for a currier company in Malaysia.